Design And Build A Mobile-Based Calligraphy And Inscription Order Customize Application With The Waterfall Method Using Fabric JS - Maulana, Alfarizi; Alda, Muhamad (Information Technology and Science (ITScience), 2024)
Mobile-based apps have become one of the most important aspects of daily life and even for spiritual and aesthetic purposes such as ordering calligraphy and inscriptions. This also had an impact on the Inscription Blessing Shop. In recent years, the demand for personalized calligraphy and inscriptions has increased significantly. However, this store experienced problems in the ordering process. The process of ordering calligraphy and inscriptions is often still done conventionally, where consumers have to come to the store to place an order which may take a long time and is inefficient. To overcome these obstacles, an effective and efficient system is needed by designing and building a mobile-based booking application. This application will be designed using the waterfall development method by utilizing Fabric JS technology as an interface design. The results of this study were obtained that a mobile-based application called the Blessing Inscription Application was formed which can order inscriptions and other carvings anywhere and anytime. The app can allow users to select different types of calligraphy fonts, set layouts, and add decorative elements. This research is expected to make a significant contribution in facilitating users' creativity and enriching their experience in designing and sharing calligraphy works and digital inscriptions.